Research progress of extended nursing and rehabilitation for motor dysfunction after stroke (脑卒中后运动功能障碍延续康复护理研究进展) - LIU Huiqin (刘慧琴); LIU Yerong (刘叶荣) (中西医结合护理)
Motor dysfunction after stroke seriously affects the quality of life of patients, but also brings a heavy burden to the family and society. The recovery degree of limb function determines the quality of life of patients. Extended nursing and rehabilitation plays an important role in the functional recovery of patients. In order to provide reference for the further research and practice of stroke rehabilitation nursing, this paper analyzed the continuing rehabilitation nursing of stroke motor dysfunction in recent years. (脑卒中后运动功能障碍严重影响患者的生活质量, 也给患者家庭和社会带来沉重负担。肢体功能的恢复程度与患者的生存质量密切相关, 而延续康复护理在患者功能恢复中起到极为重要的作用。本文对近年来脑卒中运动功能障碍的延续康复护理进行梳理分析, 以期为脑卒中延续康复护理的进一步研究及实践提供参考依据。)